2016
DOI: 10.1021/acs.est.6b00706
|View full text |Cite
|
Sign up to set email alerts
|

Occurrence of Atrazine and Related Compounds in Sediments of Upper Great Lakes

Abstract: Surface grab and core sediment samples were collected from Lakes Michigan, Superior, and Huron from 2010 to 2012, and concentrations of herbicides atrazine, simazine, and alachlor, as well as desethylatrazine (DEA), were determined. Concentrations of atrazine in surface grabs ranged from 0.01 to 1.7 ng/g dry weight and are significantly higher in the southern basin of Lake Michigan (latitude <44°) than other parts of the three lakes. The highest concentration of alachlor was found in sediments of Saginaw Bay i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
29
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 49 publications
(29 citation statements)
references
References 46 publications
0
29
0
Order By: Relevance
“…The detection of atrazine-desethyl-2-hydroxy at constant levels might be attributed to the release of atrazine (or TPs) from contaminated river sediments prior to infiltration in the RBF system. 83 Other known metabolites of atrazine and simazine were screened for in HRMS1 data, but were not detected. These TPs might have either been absent from the RBF transect or occurred at undetectable concentrations.…”
Section: Resultsmentioning
confidence: 99%
“…The detection of atrazine-desethyl-2-hydroxy at constant levels might be attributed to the release of atrazine (or TPs) from contaminated river sediments prior to infiltration in the RBF system. 83 Other known metabolites of atrazine and simazine were screened for in HRMS1 data, but were not detected. These TPs might have either been absent from the RBF transect or occurred at undetectable concentrations.…”
Section: Resultsmentioning
confidence: 99%
“…19 A recent study (2010− 2012) detected alachlor in sediments samples from the great lakes at median concentrations between 0.001 and 0.18 ng/gdry weight. 20 Metolachlor, metolachlor ESA, metolachlor OA, alachlor ESA, and alachlor were the eighth, 18th, 52nd, 150th, and 293rd, respectively, most frequently detected anthropogenic compounds in a nationwide US study of stream surface water, sampled between 2012 and 2014. 21 Thus, with their toxicity, mobility, and potential to leach into groundwater and runoff into surface waters, it is critical to monitor the nontarget impacts of chloroacetanilide herbicides on soil ecosystems.…”
Section: ■ Introductionmentioning
confidence: 95%
“…Less than 4.5 × 10 6 kg of alachlor and racemic metolachlor were estimated, while the applications of butachlor and propachlor were not reported . A recent study (2010–2012) detected alachlor in sediments samples from the great lakes at median concentrations between 0.001 and 0.18 ng/g-dry weight . Metolachlor, metolachlor ESA, metolachlor OA, alachlor ESA, and alachlor were the eighth, 18th, 52nd, 150th, and 293rd, respectively, most frequently detected anthropogenic compounds in a nationwide US study of stream surface water, sampled between 2012 and 2014 .…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, the presence of pesticide metabolites in the environment is of great concern. Desethyl-atrazine (DEA) is a metabolite formed by the physicochemical process and microbial degradation of its parent atrazine in soil, which is widely distributed in environmental media (Guo et al 2016;Yu et al 2018). Groundwater research in Iowa (USA) reported a DEA detection frequency of 32.1%, ranked only second to its parent compound atrazine (37.4%) and higher than deisopropylatrazine (DIA) (21.4%) and hydroxyatrazine (HA) (11.4%) (Kolpin et al 2000).…”
Section: Introductionmentioning
confidence: 99%